The Awareness of Sharia Financial Literacy in The Quarter-Life Phase - Alfina Rahmatia; Arief Dwi Saputra (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2021)
Nowadays, there are enormous challenges toward this era, especially the young generation between 20 and first 30 years old who will face a quarter-life crisis phase in which one of the causes is literate or not literate to finance. The grand objective of this research is to analyze gender, income per month, and marital status toward the awareness level to sharia financial literacy in the quarter-life crisis phase for IAIN Palangka Raya Alumni on 2010-2015. Primary data applied in this study are compiled from questionnaires and interviews with mixed methods. This research uses multiple regression with SPSS application, while the interview data uses descriptive analysis. The result reveals that gender and income per month have no significant influence on the awareness level of sharia financial literacy, but marital status has a significant influence on the awareness level of sharia financial literacy for IAIN Palangka Raya Alumni on 2010-2015.